Neuroprotective properties of Centella asiatica (L.) urban on combined D-galactose and aluminium chloride-induced toxicity and cognitive impairment in rats - Chiroma, Samaila Musa (2019)
Cognitive impairments and cholinergic dysfunctions have been well documented as a disorder in old age diseases including Alzheimer’s disease (AD). D-galactose (D-gal) has been reported to be a senescence agent, while aluminium acts as a neurotoxic metal, but little is known about their combined effects on rats at different doses. The plant Centella asiatica (CA) has been reported to exhibit neuroprotective effects both in vitro and in vivo models of neurodegenerative diseases. Hence, the present study established AD-like rat model of neurotoxicity and cognitive impairment induced by D-gal and aluminium chloride (AlCl3), besides exploring the potential protective effects of CA in the AD-like rat’s model. Healthy male albino wistar rats were injected with D-gal 60 mg/kg intra peritoneally (i.p), while AlCl3 (100, 200, or 300 mg/kg) was orally administered once daily for 10 consecutive weeks. Behavioural assessment, open field test (OFT) and Morris water maze (MWM) test were evaluated, along with histopathological examination of the hippocampus. Additionally, biochemical measurements of acetylcholinesterase (AChE) and phosphorylated tau protein levels (P-Tau) of the rat’s brains were also evaluated. Subsequently, another batch of rats were co-administered with D-gal 60 mg/kg and AlCl3 200 mg/kg and CA (200, 400 and 800 mg/kg) and donepezil 1 mg/kg for 10 weeks. Behavioural assessments of the rats and morphological analysis (Nissl’s staining and transmission electron microscopy) of their brains were carried out. Further, oxidative stress biomarkers (MDA and SOD), P-Tau and its synthetic proteins, apoptotic gene markers and AChE levels were also evaluated. The results revealed that rats treated with D-gal 60 + AlCl3 200 mg/kg showed cognitive impairments in both spatial and non-spatial learning and memory tests, associated with marked neuronal loss (p<0.05), oxidative stress (p<0.05) and increased AChE level (p<0.05) in their brains. Additionally, significant increase in the expression of P-Tau and GSK-3β (p<0.05) and decrease in the expression of PP2A (p<0.05) in their brains were also observed. Finally, there was also 4 folds decrease of Bcl-2 mRNA and 1.4 folds increase in the expression caspase-3 mRNA in the rat’s hippocampus. Administration of CA, and irrespective of dose alleviated the D-gal and AlCl3 induced AD-like associated pathologies in rats. These includes cognitive deficits, AChE level, oxidative stress, aberrant cytoarchitecture of the rats brains, expression of P-Tau biosynthetic proteins and expression of genes associated with intrinsic mitochondria-mediated apoptosis. Thus exhibiting neuroprotective effects which could be attributed to the synergistic action of some of CA’s active phytochemicals. All these findings provide scientific evidence to support the exploitation of CA as a safe and effective plant to consider in the fight against AD.